Automatic damage detection for sensitive cultural heritage sites - Cerra, Daniele; Tian, Jiaojiao; Lysandrou, Vasiliki; Plank, Simon (My University, 2016)
The intentional damages to local Cultural Heritage sites carried out in recent months by the Islamic State (IS) have received wide coverage from the media worldwide. Earth Observation data is an important tool to assess these damages in such non- Accessible areas: If a fast response is desired, automated image processing techniques would be needed to speed up the analysis. This paper shows the first results of applying fast and robust change detection techniques to sensitive areas. A map highlighting potentially damaged buildings is derived, which could help experts at timely assessing the damages to the Cultural Heritage sites in the observed images.
Keywords: Change detection; Cultural heritage